Revisiting the placental clock: Early corticotrophin-releasing hormone rise in recurrent preterm birth. - Christina L Herrera (Public Library of Science (PLoS), 2021)
Objective To determine if maternal plasma CRH and preterm birth history were associated with recurrent preterm birth risk in a high-risk cohort. Study design Secondary analysis of pregnant women with a prior preterm birth ≤35 weeks receiving 17-alpha hydroxyprogesterone caproate for the prevention of recurrent spontaneous preterm birth. All women with a 24-week blood sample were included. Maternal plasma CRH level at 24- and 32-weeks' gestation was measured using both enzyme-linked immunosorbent assay (ELISA) and extracted radioimmunoassay (RIA) technologies. The primary outcome was spontaneous preterm birth <37 weeks. The association of CRH, prior preterm birth history, and the two combined was assessed in relation to recurrent preterm birth risk. Results Recurrent preterm birth in this cohort of 169 women was 24.9%. Comparing women who subsequently delivered <37 versus ≥37 weeks, mean levels of CRH measured by RIA were significantly different at 24 weeks (111.1±87.5 vs. 66.1±45.4 pg/mL, P = .002) and 32 weeks (440.9±275.6 vs. 280.2±214.5 pg/mL, P = .003). The area under the receiver operating curve (AUC) at 24 and 32 weeks for (1) CRH level was 0.68 (95% CI 0.59-0.78) and 0.70 (95% CI 0.59-0.81), (2) prior preterm birth history was 0.75 (95% CI 0.67-0.83) and 0.78 (95% CI 0.69-0.87), and (3) combined was 0.81 (95% CI 0.73-0.88, P = .001) and 0.81 (95% CI 0.72-0.90, P = .01) respectively for delivery <37 weeks. CRH measured by ELISA failed to correlate with gestational age or other clinical parameters. Conclusion In women with a prior preterm birth, CRH levels were higher and had an earlier rise in women who experienced recurrent preterm birth. Second trimester CRH may be useful in identifying a sub-group of women with preterm birth due to early activation of the placenta-fetal adrenal axis. Assay methodology is a variable that contributes to difficulties in reproducibility of CRH levels in the obstetric literature.